Lung Atelectasis Promotes Immune and Barrier Dysfunction as Revealed by Transcriptome Sequencing in Female Sheep. (November 2020) - Zeng, Congli; Motta-Ribeiro, Gabriel C.; Hinoshita, Takuga; Lessa, Marcos Adriano; Winkler, Tilo; Grogg, Kira; Kingston, Nathan M.; Hutchinson, John N.; Sholl, Lynette Marie; Fang, Xiangming; Varelas, Xaralabos; Layne, Matthew D.; et al.
Abstract : Background: Pulmonary atelectasis is frequent in clinical settings. Yet there is limited mechanistic understanding and substantial clinical and biologic controversy on its consequences. The authors hypothesize that atelectasis produces local transcriptomic changes related to immunity and alveolar–capillary barrier function conducive to lung injury and further exacerbated by systemic inflammation. Methods: Female sheep underwent unilateral lung atelectasis using a left bronchial blocker and thoracotomy while the right lung was ventilated, with (n = 6) or without (n = 6) systemic lipopolysaccharide infusion. Computed tomography guided samples were harvested for NextGen RNA sequencing from atelectatic and aerated lung regions. The Wald test was used to detect differential gene expression as an absolute fold change greater than 1.5 and adjusted P value (Benjamini–Hochberg) less than 0.05. Functional analysis was performed by gene set enrichment analysis. Results: Lipopolysaccharide-unexposed atelectatic versus aerated regions presented 2, 363 differentially expressed genes. Lipopolysaccharide exposure induced 3, 767 differentially expressed genes in atelectatic lungs but only 1, 197 genes in aerated lungs relative to the corresponding lipopolysaccharide-unexposed tissues. Gene set enrichment for immune response in atelectasis versus aerated tissues yielded negative normalized enrichment scores without lipopolysaccharide (less than –1.23, adjusted P value less than 0.05) but positive scores with lipopolysaccharide (greater than 1.33, adjusted P value less than 0.05). Leukocyte-related processes ( e.g., leukocyte migration, activation, and mediated immunity) were enhanced in lipopolysaccharide-exposed atelectasis partly through interferon-stimulated genes. Furthermore, atelectasis was associated with negatively enriched gene sets involving alveolar–capillary barrier function irrespective of lipopolysaccharide (normalized enrichment scores less than –1.35, adjusted P value less than 0.05). Yes-associated protein signaling was dysregulated with lower nuclear distribution in atelectatic versus aerated lung (lipopolysaccharide-unexposed: 10.0 ± 4.2 versus 13.4 ± 4.2 arbitrary units, lipopolysaccharide-exposed: 8.1 ± 2.0 versus 11.3 ± 2.4 arbitrary units, effect of lung aeration, P = 0.003). Conclusions: Atelectasis dysregulates the local pulmonary transcriptome with negatively enriched immune response and alveolar–capillary barrier function. Systemic lipopolysaccharide converts the transcriptomic immune response into positive enrichment but does not affect local barrier function transcriptomics. Interferon-stimulated genes and Yes-associated protein might be novel candidate targets for atelectasis-associated injury. Abstract : Atelectasis alone dysregulated the local pulmonary transcriptome with negatively enriched immune response and alveolar–capillary barrier function. With associated systemic inflammation, the local immune response was positively enhanced while barrier function response remained negatively enriched. Interferon-simulated genes and Yes-associated protein appear to have important regulatory roles and may be novel candidate targets for therapy of atelectasis-associated injury.Supplemental Digital Content is available in the text.